2019
DOI: 10.1029/2018jd029382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cold Ocean Eddy on Local Atmospheric Boundary Layer Near the Kuroshio Extension: In Situ Observations and Model Experiments

Abstract: Shipboard observations captured clear modulations of the marine atmospheric boundary layer (MABL) over a 300‐km‐diameter cold eddy in the Kuroshio Extension in April 2014. Regional atmospheric model experiments, with 30‐km and 10‐km horizontal resolutions for outer and inner domains, respectively, are conducted to aid the interpretations of the in situ observations. Enhanced turbulent heat fluxes promoted a well‐mixed MABL up to 1900‐m deep and a stratocumulus layer over the warm water west of the eddy. Over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The results indicated that the MOEs-induced cloud and precipitation anomalies were 3.6% and 7.5% of the background values, respectively. In addition, field observations and numerical experiments showed that MOEs affect the development of clouds over them [14][15][16]. The vertical mixing and pressure adjustment mechanisms generate wind divergence anomalies, modifying the vertical motion and thus influencing the clouds and precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the MOEs-induced cloud and precipitation anomalies were 3.6% and 7.5% of the background values, respectively. In addition, field observations and numerical experiments showed that MOEs affect the development of clouds over them [14][15][16]. The vertical mixing and pressure adjustment mechanisms generate wind divergence anomalies, modifying the vertical motion and thus influencing the clouds and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The MOEs in the North Pacific, characterized by strong eddy kinetic energy (EKE) [17], are prevalent in the KE region and subtropical countercurrent (STCC) region (Figure 1a). Through previous analyses of satellite data, reanalysis data, observation data and numerical simulation results, the existing literature has elucidated the atmospheric responses to the MOEs in the KE region [12][13][14][15]18,19]. In the STCC region, by analyzing satellite data, Chow and Liu (2013) [20] found that there were phase differences between the centers of SSTAs and the centers of MOEs in the spring, while the surface wind speed anomalies (SWSAs) pattern bears a discernable resemblance to the SSTAs pattern.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the response of oceanic low‐level cloud properties to the SST front, we use the WRF model, version 4.0 (Skamarock et al, 2008, 2019), which is a nonhydrostatic atmospheric model. The WRF has been used in numerous studies to investigate the effect of oceans on regional atmospheric circulation (Kilpatrick et al, 2014, 2016), precipitation systems (Tanimoto et al, 2011; Xu et al, 2010), and cloud (Jiang et al, 2019; Y. Kawai et al, 2015). In this study, we use the WRF model to investigate the response of low‐level cloud to the presence of an SST front.…”
Section: Methodsmentioning
confidence: 99%
“…Although the active role of SST fronts in summertime may not be substantial, recent studies based on ship‐based and satellite observations indicated that the SST front modulates the atmospheric boundary layer and low‐level clouds overlying it (Jiang et al, 2019; Liu et al, 2014; Miyamoto et al, 2018; Tokinaga et al, 2009; Y. Kawai et al, 2015, 2019). There are local effects of the SST anomaly associated with the front on the low‐level cloud and atmospheric boundary layer, such as thickness and turbulent mixing, in summertime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation